Разработка энергоэффективного асинхронного электропривода для перемежающегося режима работы - Петрушин, Виктор Сергеевич; Плоткин, Юрий Романович; Еноктаев, Ростислав Николаевич; Бендахман, Бухалфа (Национальный технический университет "Харьковский политехнический институт", 2019)
Рассматривается электропривод, включающий в себя кроме асинхронного короткозамкнутого двигателя, согласующий редуктор. Нагрузку привода определяет заданная циклограмма, представляющая собой изменение нагрузочных моментов во времени. Улучшение эксплуатационных характеристик электропривода обеспечивается за счёт оптимизационного перепроектирования двигателя. В качестве критериев оптимизации используются среднециклические коэффициенты полезного действия и мощности. Выполнен анализ энергетических,тепловых, механических и виброакустических показателей двигателей при работе на заданную циклограмму нагрузки.

The purpose of this work is the development of energy–efficient asynchronous electric drive for intermittent operation mode by using algorithms for modeling the dynamic modes of induction motors in drives with matchingreducers. A motor drive is considered, which includes, in addition to an short–circuited induction motor, a matching reducer. The load of the drive is determined by a given cyclogram, which is a change in the load moments in time. Taken into account the inconstancy of the equivalent circuit parameters of the engine associated with the change in the magnetic circuit saturation and displacement current in the rotor winding, and the availability of higher spatial harmonics in the magnetic field. The purpose is achieved by improving the performance of the electric drive, which is provided by optimizing engine redesign, based on algorithms for modeling dynamic operating modes of the drive. A methods is proposed in which the average cyclic efficiency and power factors are used as optimization criteria. They aredetermined by the dependencies of the drive efficiency and motor power factor, which are found for the cycle in question, takinginto account dynamic modes, with the addition of electrical losses taking into account the main and additional losses in the magnetic circuit, mechanical and additional. The dynamic characteristics of the consume currents and powers by the basic and optimized motors are obtained and compared. The greatest effect (the energy efficiency ratio, which is the product of the engine powerfactor and the efficiency of the engine and matching reducer, rises from 0,528 to 0,613) is achieved with two–criterion optimization with weighting coefficient of criteria 0,5. The simulation of the thermal state of the motors was carried out and the overheating temperatures of the stator windings of the basic and optimized motors were determined. The mechanical indicators, which characterize the mechanical state of the motors, are compared. The analysis of vibroacoustic indicators of the engines was performedwhen operating for a given load cyclogram: vibration speed and vibrationacceleration of magnetic origin, vibration velocity of mechanical origin, ventilation and magnetic noise.
Development of energy–efficient asynchronous electric drive for intermittent operation
Keywords: асинхронный двигатель; циклограмма нагрузки; математическая модель; среднециклические критерии; коэффициент энергетической эффективности; тепловое состояние; виброакустические показатели; механическое состояние; induction motor; load cyclogram; mathematical model; average-cyclic criteria; energy efficiency coefficient; thermal state; vibroacoustic indicators; mechanical condition